The Phenomena of "Psychological Inheritance" and "Generational Inheritance" In the Context of Psychological Research (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The human factor and the problem of its origin have been of scientific interest to thinkers since ancient times. Until recently, religious approaches provided the most reliable explanation of the nature of this problem for the majority of human society. Today, few people take seriously the idea of ​​a divine origin of goodness. Goodness is transmitted from generation to generation in social continuity by ancestors through spiritual, educational and moral principles in the process of education.